Integration of crossbred dairy goats into Burundi's farming systems - Rey, B. (Inter-American Institute for Cooperation on Agriculture, 1995)
The Ngozi goat project promoted a new livestock system by introducing a new genotype and improving housing, feeding, health and marketing. To assess and monitor its impact, a collaboration with the International Livestock Center for Africa was initiated in 1989. The aim of this collaboration is to gather results from an analysis of a running trend, using case studies in areas where Development projects have introduced crossbred dairy goats in the farming system over a relatively long period and assessing the productivity and role of dairy goats in systems where they are the object of a Development effort. The systems approach adopted to study the key issue of the genetic component is discussed.